Shamans, Violence, and the Reconstruction of Memory: Violence Surrounding Witchcraft Accusations in Banyuwangi, 1998–1999 - Latif Kusairi; Dhanang Respati Puguh; Yety Rocwulaningsih (Islam Realitas: Journal of Islamic and Social Studies, 2025)
This article examines the wave of violence triggered by accusations of witchcraft (dukun santet) in Banyuwangi between 1998 and 1999, which resulted in more than 194 deaths. The killings emerged amid the political, economic, and social crises preceding the collapse of Indonesia’s New Order regime. Accusations of santet were not merely expressions of popular belief but were actively produced and instrumentalized as tools of mass mobilization. Political stigmatization that associated alleged witches with communism, combined with the interests of both local and supra-local actors, significantly accelerated the scale and spread of violence. The study analyzes the relationship between witchcraft accusations and violent mobilization during a period of political transition by mapping key actors, networks, and patterns of action. It further examines how myths, rumors, and collective imaginaries functioned to legitimize killing. In addition, the article assesses the broader socio-cultural consequences of the killings, particularly their impact on civic identity, collective memory, and shifting configurations of power in the Reformasi era. Methodologically, the research combines empirical analysis and theoretical reflection, drawing on Charles Tilly’s concept of violence and Claude Lévi-Strauss’s theory of myth. Primary sources include court and police records, the East Java Regional Archives, reports from the National Commission on Human Rights (Komnas HAM), and contemporary mass media coverage. The findings show that political, economic, and cultural dynamics shaped violence and effects on Banyuwangi’s social identity and collective memory. Artikel ini mengkaji gelombang kekerasan yang dipicu oleh tuduhan ilmu sihir (dukun santet) di Banyuwangi pada 1998-1999 yang mengakibatkan lebih dari 194 kematian. Pembunuhan-pembunuhan tersebut terjadi di tengah krisis politik, ekonomi, dan sosial menjelang runtuhnya rezim Orde Baru di Indonesia. Tuduhan santet tidak semata-mata merupakan ekspresi kepercayaan popular, melainkan secara aktif diproduksi dan dimanfaatkan sebagai sarana mobilisasi massa. Stigmatisasi politik yang mengaitkan para terduga penyihir dengan komunisme, yang dikombinasikan dengan kepentingan aktor-aktor lokal dan supra-lokal, berperan besar dalam mempercepat dan memperluas eskalasi kekerasan. Penelitian ini bertujuan mengungkap hubungan antara tuduhan santet dan mobilisasi kekerasan masa transisi politik, memetakan aktor-aktor kunci, jaringan, dan pola-pola tindakan. Lebih lanjut, artikel ini menganalisis bagaimana mitos, rumor, serta imajinasi kolektif berfungsi untuk melegitimasi pembunuhan. Selain itu, studi ini menilai dampak sosial-budaya yang lebih luas dari pembunuhan tersebut, khususnya terhadap identitas kewargaan, ingatan kolektif, dan perubahan konfigurasi kekuasaan pada era Reformasi. Secara metodologis, penelitian ini menggabungkan analisis empiris dan refleksi teoretis, dengan merujuk pada konsep kekerasan kolektif Charles Tilly dan teori mitos Claude Lévi-Strauss. Sumber-sumber primer meliputi arsip pengadilan dan kepolisian, Arsip Daerah Jawa Timur, laporan Komisi Nasional Hak Asasi Manusia (Komnas HAM), serta pemberitaan media massa sezaman. Temuan penelitian menunjukkan bahwa dinamika politik, ekonomi, dan sosial-budaya membentuk kekerasan tersebut serta berdampak pada identitas social dan memori kolektif masyarakat Banyuwangi.